Development of The Prudence Scale - Hamna Zahid, Bushra Irshad, Mamoona Khan, Qurrat Ul Ain Tahira, Rehana Akram, Noor Fatima Ali, Saira Maqsood, Dr. Iffat Batool (Migration Letters, 2024)
The present study had three objectives; to conceptualize the construct- prudence, to develop an indigenous scale on prudence and to establish its psychometric properties i.e., reliability and validity. This study used sequential exploratory research design with was divided into further sub-studies. The first study used a qualitative approach to employ thematic analysis on the semi-structured interviews conducted on N=10 participants. Eight themes emerged through thematic analysis which were self-control, morality, informed decision making, wisdom, cultural prudence, religious aspect, consequences, and practice. Study 2 comprised of quantitative approach to generate, refine, and finalize item pool. 30 out of 40 items were retained based on reliability. Assumptions of sample size were fulfilled as showed by the results of KMO and Bartlett’s test of sphericity. 27 items were finally retained through Varimax rotation in EFA, with the four dimensions: Insight, social and family determinants, diligence, and decision making. In study 3, CFA analysis showed acceptable fit indices i.e., GFI= .90, CFI= .97, AGFI= .90 and RMSEA= .06. The reliability of the scale was also satisfactory, and the validity was established through the AVE method. An indigenous tool on prudence would serve an integral contribution in research and importance of collective effort from individuals, communities, leaders, and institutions to promote a culture of thoughtful consideration and ethical behavior.